Cutaneous lupus concerns from the patient perspective: a qualitative study - Victoria P Werth; Rui Feng; Daisy Yan; Sarah Ahmed; Srita Chakka; Danielle Zamalin; Rebecca Krain; Josef Concha; Joyce Okawa (Lupus Science and Medicine)
Objective There is a need to identify concerns unique to patients with cutaneous lupus erythematosus (CLE), which may not be captured by current common-practice dermatological quality-of-life tools. This study formally characterises what bothers patients with CLE about their disease by conducting semistructured, qualitative interviews.Methods Sixteen patients with CLE were interviewed about how their cutaneous findings impact their daily life. Each interview was transcribed, coded and categorised for recurrent themes. Current CLE activity and damage were also assessed by the Cutaneous Lupus Activity and Severity Index tool.Results Responses were categorised into six themes, including Fear of Disease Progression, Unwanted Attention, Self-Consciousness, Physical Signs/Symptoms, Emotional Symptoms and Functional Decline. The most commonly reported themes were Self-Consciousness, mentioned by 13 of 16 (81.3%) patients, Physical Symptoms, mentioned by 12 of 16 (75%), and then Fear of Disease Progression, by 11 of 16 (68.8%). Frequently mentioned physical signs/symptoms included erythema, itch, dyspigmentation, scar and alopecia. The physical signs/symptoms were categorised as activity signs/symptoms, damage signs and other. For activity signs, erythema was mentioned most frequently (5 of 16), then scale (2 of 16). For activity symptoms, itch was mentioned most frequently (6 of 16), then pain (5 of 16). For damage signs, dyspigmentation was mentioned most frequently (4 of 16), followed by scarring (3 of 16). Patients less than 60 years old were more likely to report emotional symptoms than older patients (p<0.05), but there was no significant variation in frequency of reported themes between race, sex or subtype of CLE.Conclusions These patient experiences and resultant themes elucidated by this study are worth noting in future standardised estimations of the quality of life of patients with CLE. Additionally, the concerns shown by these interviews are important topics for providers to discuss when evaluating patient disease progression.